Perspectives on the Happiness of Community-Dwelling Elderly in Korea - Jeon, Sang Won (Psychiatry Investig, 2016)
OBJECTIVE: A community survey was performed to investigate the factors and perspectives associated with happiness among the elderly in Korea (≥60 years). METHODS: Eight hundred volunteers selected from participants in the Ansan Geriatric study (AGE study) were enrolled, and 706 completed the survey. The Happiness Questionnaire (HQ), which asks four questions about happiness, was administered. To explore the relationship between happiness and depression, the Geriatric Depression Scale (GDS) and the Beck Depression Inventory (BDI) also were administered. RESULTS: The participants' average level of happiness, determined using a 100-mm visual analogue scale (VAS) of the HQ, was 64.7±26.0. The happiest situations for most people were "getting together with family" (23.8%) and "living in peace with family members (well-being)" (13.2%). Frequent reasons for not being happy were "worsened health condition" (28.7% of the not-happy group), "economic problems of their own" (16.5%), and "economic problems of their children" (14.8%). The participants' choices regarding the essential conditions for happiness were "good health" (65.3%) and "being with family" (20.5%). The BDI and GDS scores were negatively related to the happiness score. A preliminary scale [Happy (Haeng-Bok, 幸福) aging scale] based on the HQ for measuring the happiness level of the Korean elderly was suggested for follow-up studies. CONCLUSION: The most important factors determining the happiness of the community-dwelling elderly in Korea were good family relationships, economic stability, and good health. A higher depression score negatively impacted happiness among Korean elders. Further studies on the factors in their happiness are required.